The Burden of Respiratory Syncytial Virus Infection in the Young - Resch, Bernhard (IntechOpen, 2019)
Respiratory syncytial virus (RSV) causes seasonal epidemics during the winter and wet seasons, particularly in young children. Although there is one drug available for prophylaxis, palivizumab, it is indicated for high-risk children only. Therefore a vaccine is urgently needed. This book provides an overview of RSV and discusses its incidence and presentation in different populations, including preterm infants and children with congenital heart disease. It also discusses future strategies for RSV prophylaxis and developments in and barriers to creating a viable vaccine.